2018
DOI: 10.5194/bg-2017-565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutrient availability and the ultimate control of the biological carbon pump in the Western Tropical South Pacific Ocean

Abstract: 15Surface waters (0-200 m) of the western tropical South Pacific (WTSP) were sampled along a longitudinal 4000 km transect (OUTPACE cruise, 18 Feb., 3 Apr. 2015) during the stratified period between the Melanesian Archipelago (MA) and the western part of the SP gyre (WGY). Two distinct areas were considered for the MA, the western MA (WMA) and the eastern MA (EMA). The main carbon (C), nitrogen (N), phosphorus (P) pools and fluxes allow for characterization of the expected trend from oligotrophy to ultra-olig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 62 publications
(92 reference statements)
2
18
0
Order By: Relevance
“…However, two other main processes can contribute to export: physical mixing resulting in export of dissolved organic matter (Carlson et al, 1994;Carlson and Ducklow, 1995;Copin-Montégut and Avril, 1993;Toggweiler, 1989) and zooplankton diel migrations that actively transport organic matter out of the photic layer (Longhurst et al, 1989(Longhurst et al, , 1990Longhurst and Glen Harrison, 1988;Vinogradov, 1970). In the present study, the DON export flux was limited to eddy diffusion as we performed our survey during the stratification period, and the low downward flux of DON estimated by Moutin et al (2018) was unable to explain the observed imbalance. However, zooplankton might play a significant role, although it is hard to quantify.…”
Section: Disequilibrium Of New Vs Exported Productionmentioning
confidence: 94%
“…However, two other main processes can contribute to export: physical mixing resulting in export of dissolved organic matter (Carlson et al, 1994;Carlson and Ducklow, 1995;Copin-Montégut and Avril, 1993;Toggweiler, 1989) and zooplankton diel migrations that actively transport organic matter out of the photic layer (Longhurst et al, 1989(Longhurst et al, , 1990Longhurst and Glen Harrison, 1988;Vinogradov, 1970). In the present study, the DON export flux was limited to eddy diffusion as we performed our survey during the stratification period, and the low downward flux of DON estimated by Moutin et al (2018) was unable to explain the observed imbalance. However, zooplankton might play a significant role, although it is hard to quantify.…”
Section: Disequilibrium Of New Vs Exported Productionmentioning
confidence: 94%
“…In addition to the measurements of chlorophyll a, BP, PP, T DIP and DOC described below, other data presented in this paper include hydrographic properties, nutrients and N 2 fix, for which detailed protocols of analysis and considerations for methodology are available in Moutin et al (2017Moutin et al ( , 2018 and Bonnet et al (2018). Briefly, DIP and nitrate concentrations were measured using standard colorimetric procedures on a AA3 AutoAnalyzer (Seal-Analytical).…”
Section: Sampling Strategymentioning
confidence: 99%
“…The overall correlation between in vivo fluorescence (Chl iv) and Chl a was very patchy (Chl a = 1.582 × Chl iv + 0.0241, n = 169, r = 0.61). This is due to the heterogeneity at the time of sampling and the nature of the populations present, i.e., essentially different fluorescence yields over depth and species (Neveux et al, 2010). Thus in vivo fluorescence was used only to track high-frequency variability at the LD sites, the shape of a vertical profile's distributions and the location of the dcm, as well as longitudinal trends.…”
Section: Chlorophyll Amentioning
confidence: 99%
“…Alvarez et al, 2009, Carter et al, 2017. For the OUTPACE area, Moutin et al (2018) shows that the mixed layer depth do not exceed 70 m in the area. Even if the depth of the deep chlorophyll maximum was encountered below 100 dbar along the transect, we will consider CANT values up to 100 dbar.…”
Section: Hydrological Context Along the Outpace Transectmentioning
confidence: 99%
“…The difference between these sub-regions is evidenced by the difference in oligotrophy . Due to specific conditions in the transition area between the MA and WGY , SD11, SD12 and LDB were discarded from both groups in this study following the arguments in Moutin et al (2018). TrOCA is a source of significant errors but also that even with regionally "tunned" parameters a global bias in the method exists.…”
Section: Hydrological Context Along the Outpace Transectmentioning
confidence: 99%